2021
DOI: 10.1021/acs.chemrestox.1c00020
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Water- and Organic-Soluble Wood Tar Fractions from Biomass Burning in Lung Epithelial Cells

Abstract: Widespread smoke from wildfires and biomass burning contributes to air pollution and the deterioration of air quality and human health. A common and major emission of biomass burning, often found in collected smoke particles, is spherical wood tar particles, also known as “tar balls”. However, the toxicity of wood tar particles and the mechanisms that govern their health impacts and the impact of their complicated chemical matrix are not fully elucidated. To address these questions, we generated wood tar mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…All tests were performed in A549 cells, a commonly used tumorigenic cell line. Pardo et al [13] compared the toxicity of wood tar materials in both A549 and BEAS-2B cells, finding that BEAS-2B were slightly less responsive to the toxic effects of biomass burning than A549. Other studies, however, stated that BEAS-2B is more responsive to toxicity than A549 [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All tests were performed in A549 cells, a commonly used tumorigenic cell line. Pardo et al [13] compared the toxicity of wood tar materials in both A549 and BEAS-2B cells, finding that BEAS-2B were slightly less responsive to the toxic effects of biomass burning than A549. Other studies, however, stated that BEAS-2B is more responsive to toxicity than A549 [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, stated that BEAS-2B is more responsive to toxicity than A549 [31,32]. Pardo et al [13] justify the use of A549 cells by stating that BEAS-2B cells are immortalized by integrated SV40 virus and present a low sensitivity, suggesting that the choice of BEAS-2B over A549 is disputable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in 2021 contributed to strengthening the evidence that PM 2.5 from wildfire smoke-which may contain residue from burned buildings and other materials-is also more toxic than ambient PM 2.5 . A review highlighted that wildfire smoke contains many of the carcinogenic components of cigarette smoke 39 , and an experimental study found it to induce both oxidative stress and DNA damage 40 . An observational study in Southern California found 10-fold more respiratory hospitalizations in those exposed to wildfire PM 2.5 compared to those exposed to the same amount of ambient PM 2.5…”
Section: Wildfire Smoke: "Airpocalypse"mentioning
confidence: 99%
“…A549 cells are one of the most commonly used cell lines for in vitro research on the mechanisms of PM health effects, 24,25 and studies comparing A549 and non-cancerous human lung epithelial cells have observed similar trends in toxicities of different PM samples. 26,27 The cells were grown in a humidied atmosphere with 5% CO 2 at 37 C.…”
Section: àmentioning
confidence: 99%